Situational modeling of distributed informational system fragments - Сосновский, Юрий Вячеславович (Eastern-European Journal of Enterprise Technologies, 2013)
The solution of the problem of processing of rapidly growing volumes of information is the application of distributed information systems. As the heterogeneity of the system increases, the role of mechanisms of optimization increases also, and their application can significantly improve the efficiency of data processing. To model gridsystems, a whole series of programs-simulators were created. At the same time, many of them are either unavailable or solve a narrow range of problems. The article describes the process of creation of a model in the simulator GridSim, and presents a number of formalized situations, which differ by the number of instructions and the size of input and output files. The modeling for fragments of the grid-system allows you choosing the most appropriate cluster for problems packet processing on the basis of the specified limits. The restrictions can be simple (for example, minimization of the time spent in the system), and composite.